Letter from William Randolph Hearst to Julia Morgan, August 1920 - William Randolph Hearst::::::author::: (1920)
Charles E. Birge was an architect who worked on commercial and residential projects for William Randolph Hearst in New York. He designed the Clarendon. The letter is undated, but a researcher dated to possibly August 1920.